ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN PADA CAHAYA PUTRI MEUBEL DESA LAWULO KECAMATAN SAMATURU PERIODE TAHUN 2024 - Biringkaka, Wahida; Triani, Neks; Chairunnas, Arnadi (Jurnal Akuntansi Kompetif, 2025)
This study was designed to examine the implementation of a sales accounting information system at Cahaya Putri Meubel, located in Lawulo Village, Samaturu District. In this study, a qualitative approach with a descriptive method was used. Data collection was conducted through observation, direct interviews with the business owner, and document collection. The study results indicate that the current sales accounting information system is still manual and primitive, relying on notebooks and receipts without a computer-based system. This leads to risks of transaction data loss, inaccuracies in record-keeping, and potential task duplication.